Clinical and Kinematic Features of Valproate-Induced Tremor and Differences with Essential Tremor - Paparella, Giulia (Cerebellum, 2020)
Tremor is a common movement disorder that can be induced by medications, including valproate, which is used for the treatment of epilepsy. However, the clinical and neurophysiological features of valproate-induced tremor are still under-investigated. We performed a clinical and kinematic assessment of valproate-induced tremor by considering tremor body distribution and activation conditions. We investigated possible correlations between demographic and clinical data and kinematic features. Valproate-induced tremor results were also compared with those collected in a large sample of patients with essential tremor. Sixteen valproate-induced tremor patients and 93 essential tremor patients were enrolled. All participants underwent a standardised neurological examination and video recording. Patients also underwent an objective assessment of postural, kinetic and rest tremor of the upper limbs and head tremor through kinematic analysis. Nonparametric tests were used for statistical comparisons between the two groups. Clinical evaluation showed a higher occurrence of rest tremor as well as head or voice, and lower limb involvement in patients with valproate-induced tremor. Kinematic analysis showed a substantial variability in the tremor features of patients with valproate-induced tremor. Compared to essential tremor, we found a higher occurrence of rest tremor of the upper limbs and the involvement of more body segments in valproate-induced tremor patients. Valproate-induced tremor has distinctive clinical and kinematic features, which may suggest that valproate interferes with the cerebellar functions. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s12311-020-01216-5.